Unilateral biportal endoscopic decompression combined with percutaneous pedicle screw fixation offers new treatment option for thoracolumbar burst fractures with secondary spinal stenosis - Guangchao Bai; Xiaowen Qiu; Guojun Wei; Xiaowei Jing; Qingfeng Hu (Scientific Reports)
Abstract The purpose of this study was to present the surgical technique of Unilateral Biportal Endoscopic (UBE) decompression combined with percutaneous pedicle screws for the treatment of thoracolumbar burst fractures with secondary spinal stenosis. Thoracolumbar burst fracture is a common traumatic disease in spinal surgery. In the Arbeitsgemeinschaft für Osteosynthesefragen (AO) classification of thoracolumbar fractures, Type A fractures have the highest incidence, accounting for about 70%, with A1 and A3 types being the most common1. In Type A3 fractures, there is often a displacement of fracture fragments into the spinal canal, leading to secondary spinal stenosis. The traditional approach is posterior open surgery pedicle screws combined with direct visualization for decompression, which requires extensive stripping of paravertebral muscles and resection of more bone, and is more traumatic2, which is not in line with the current development concept of minimally invasive spine. The UBE technique in spinal endoscopy is currently a hot spot in the development of minimally invasive spine3, and we attempted to utilize UBE decompression combined with percutaneous pedicle screws to treat thoracolumbar burst fracture with spinal stenosis, which provides a new option for the surgical treatment of thoracolumbar burst fracture with secondary spinal stenosis. We included five patients with thoracolumbar burst fractures with secondary spinal stenosis admitted to our hospital between January 2023 and January 2024, who were treated with UBE decompression combined with percutaneous pedicle screw internal fixation by our team. The degree of correction of spinal deformity was assessed using the sagittal Cobb angle and the percentage of height of the anterior margin of the vertebral body, the rate of canal encroachment was used to assess the decompression of the spinal canal, and the recovery of the patients’ ability to live was assessed using the Visual Analogue Scale (VAS) and Japanese Orthopaedic Association (JOA) Score. The results showed that the average operative length of the patients was 154.2 min, and the average intraoperative bleeding was 90 ml; the sagittal Cobb angle averaged 22.23° preoperatively, and 6.10° at 3 days postoperatively; the anterior vertebral body height ratio averaged 36.77% preoperatively, and 91.16% at 3 days postoperatively; and the residual spinal canal volume averaged 52.01% preoperatively, and 91.58% at 3 days postoperatively; VAS score averaged 7 preoperatively and 2 at 3 days postoperatively; JOA score averaged 8.4 preoperatively and 22.4 at 3 days postoperatively. UBE decompression combined with percutaneous pedicle screws is effective in the treatment of thoracolumbar burst fractures with secondary spinal stenosis and is a safe, minimally invasive surgical option for this patient population.